Q methodology for post-social-turn research in SLA - Irie, Kay (Studies in Second Language Learning and Teaching, 2014)
Q methodology, an approach to inquiry on the subjective views about a complex phenomenon/issue which has been increasingly employed in a wide range of social science fields has not yet been applied in language learning and teaching research. It is a unique approach that has characteristics of both qualitative and quantitative research methods. The purpose of the present paper is to introduce Q methodology as an alternative approach and demonstrate its potential to respond to the needs of the field that has been expanding in its epistemological diversity since the social turn (Block, 2003; Ortega, 2012). The relevance of the methodology for SLA research will be discussed with a particular focus on the parallels between the development of the methodology in the 1930s and current criticisms towards the traditional cognitive approach in SLA. Using a published study (Irie & Ryan, 2014), the author explains how the focus on the holistic understanding of subjectivity is built into the procedure. Suggestions for possible areas of research and teaching in which Q methodology could be applied are discussed.